## Engage NY Eureka Math 5th Grade Module 3 Lesson 5 Answer Key

### Eureka Math Grade 5 Module 3 Lesson 5 Sprint Answer Key

A

Subtracting Fractions from a Whole Number

Question 1.

4 – \(\frac{1}{2}\) =

Answer:

4 – \(\frac{1}{2}\) = 3\(\frac{1}{2}\)

Explanation :

4 – \(\frac{1}{2}\) = \(\frac{8}{2}\) – \(\frac{1}{2}\) = \(\frac{7}{2}\) = 3\(\frac{1}{2}\)

Question 2.

3 – \(\frac{1}{2}\) =

Answer:

3 – \(\frac{1}{2}\) = 2\(\frac{1}{2}\)

Explanation :

3 – \(\frac{1}{2}\) = \(\frac{6}{2}\) – \(\frac{1}{2}\) = \(\frac{5}{2}\) = 2\(\frac{1}{2}\)

Question 3.

2 – \(\frac{1}{2}\) =

Answer:

2 – \(\frac{1}{2}\) = 1\(\frac{1}{2}\)

Explanation :

2 – \(\frac{1}{2}\) = \(\frac{4}{2}\) – \(\frac{1}{2}\) = \(\frac{3}{2}\) = 1\(\frac{1}{2}\)

Question 4.

1 – \(\frac{1}{2}\) =

Answer:

1 – \(\frac{1}{2}\) = \(\frac{1}{2}\)

Explanation :

1 – \(\frac{1}{2}\) = \(\frac{2}{2}\) – \(\frac{1}{2}\) = \(\frac{1}{2}\)

Question 5.

1 – \(\frac{1}{3}\) =

Answer:

1 – \(\frac{1}{3}\) = \(\frac{2}{3}\)

Explanation :

1 – \(\frac{1}{3}\) = \(\frac{3}{3}\) – \(\frac{1}{3}\) = \(\frac{2}{3}\)

Question 6.

2 – \(\frac{1}{3}\) =

Answer:

2 – \(\frac{1}{3}\) = 1\(\frac{2}{3}\)

Explanation :

2 – \(\frac{1}{3}\) = \(\frac{6}{3}\) – \(\frac{1}{3}\) = \(\frac{5}{3}\) = 1\(\frac{2}{3}\)

Question 7.

4 – \(\frac{1}{3}\) =

Answer:

4 – \(\frac{1}{3}\) = 3\(\frac{2}{3}\)

Explanation :

4 – \(\frac{1}{3}\) = \(\frac{12}{3}\) – \(\frac{1}{3}\) = \(\frac{11}{3}\) = 3\(\frac{2}{3}\)

Question 8.

4 – \(\frac{2}{3}\) =

Answer:

4 – \(\frac{2}{3}\) = 3\(\frac{1}{3}\)

Explanation :

4 – \(\frac{2}{3}\) = \(\frac{12}{3}\) – \(\frac{2}{3}\) = \(\frac{10}{3}\) = 3\(\frac{1}{3}\)

Question 9.

2 – \(\frac{2}{3}\) =

Answer:

2 – \(\frac{1}{3}\) = 1\(\frac{2}{3}\)

Explanation :

2 – \(\frac{1}{3}\) = \(\frac{6}{3}\) – \(\frac{1}{3}\) = \(\frac{5}{3}\) = 1\(\frac{2}{3}\)

Question 10.

2 – \(\frac{1}{4}\) =

Answer:

2 – \(\frac{1}{4}\) = 1\(\frac{3}{4}\)

Explanation :

2 – \(\frac{1}{4}\) = \(\frac{8}{4}\) – \(\frac{1}{4}\) = \(\frac{7}{4}\) = 1\(\frac{3}{4}\)

Question 11.

2 – \(\frac{3}{4}\) =

Answer:

2 – \(\frac{3}{4}\) = 1\(\frac{1}{4}\)

Explanation :

2 – \(\frac{3}{4}\) = \(\frac{8}{4}\) – \(\frac{3}{4}\) = \(\frac{5}{4}\) = 1\(\frac{1}{4}\)

Question 12.

3 – \(\frac{3}{4}\) =

Answer:

3 – \(\frac{3}{4}\) = 2\(\frac{1}{4}\)

Explanation :

3 – \(\frac{3}{4}\) = \(\frac{12}{4}\) – \(\frac{3}{4}\) = \(\frac{9}{4}\) = 2\(\frac{1}{4}\)

Question 13.

3 – \(\frac{1}{4}\) =

Answer:

3 – \(\frac{1}{4}\) = 2\(\frac{3}{4}\)

Explanation :

3 – \(\frac{1}{4}\) = \(\frac{12}{4}\) – \(\frac{1}{4}\) = \(\frac{11}{4}\) = 2\(\frac{3}{4}\)

Question 14.

4 – \(\frac{3}{4}\) =

Answer:

4 – \(\frac{3}{4}\) = 3\(\frac{1}{4}\)

Explanation :

4 – \(\frac{3}{4}\) = \(\frac{16}{4}\) – \(\frac{3}{4}\) = \(\frac{13}{4}\) = 3\(\frac{1}{4}\)

Question 15.

2 – \(\frac{1}{10}\) =

Answer:

2 – \(\frac{1}{10}\) = 1\(\frac{9}{10}\)

Explanation :

2 – \(\frac{1}{10}\) = \(\frac{20}{10}\) – \(\frac{1}{10}\) = \(\frac{19}{10}\) = 1\(\frac{9}{10}\)

Question 16.

3 – \(\frac{9}{10}\) =

Answer:

3 – \(\frac{9}{10}\) = 2\(\frac{1}{10}\)

Explanation :

3 – \(\frac{9}{10}\) = \(\frac{30}{10}\) – \(\frac{9}{10}\) = \(\frac{21}{10}\) = 2\(\frac{1}{10}\)

Question 17.

2 – \(\frac{7}{10}\) =

Answer:

Answer:

2 – \(\frac{7}{10}\) = 1\(\frac{3}{10}\)

Explanation :

2 – \(\frac{7}{10}\) = \(\frac{20}{10}\) – \(\frac{7}{10}\) = \(\frac{13}{10}\) = 1\(\frac{3}{10}\)

Question 18.

4 – \(\frac{3}{10}\) =

Answer:

4 – \(\frac{1}{10}\) = 3\(\frac{9}{10}\)

Explanation :

4 – \(\frac{1}{10}\) = \(\frac{40}{10}\) – \(\frac{1}{10}\) = \(\frac{39}{10}\) = 3\(\frac{9}{10}\)

Question 19.

3 – \(\frac{1}{5}\) =

Answer:

3 – \(\frac{1}{5}\) = 2\(\frac{4}{5}\)

Explanation :

3 – \(\frac{1}{5}\) = \(\frac{15}{5}\) – \(\frac{1}{5}\) = \(\frac{14}{5}\) = 2\(\frac{4}{5}\)

Question 20.

3 – \(\frac{2}{5}\) =

Answer:

3 – \(\frac{2}{5}\) = 2\(\frac{3}{5}\)

Explanation :

3 – \(\frac{2}{5}\) = \(\frac{15}{5}\) – \(\frac{2}{5}\) = \(\frac{13}{5}\) = 2\(\frac{3}{5}\)

Question 21.

3 – \(\frac{4}{5}\) =

Answer:

3 – \(\frac{4}{5}\) = 2\(\frac{1}{5}\)

Explanation :

3 – \(\frac{4}{5}\) = \(\frac{15}{5}\) – \(\frac{4}{5}\) = \(\frac{11}{5}\) = 2\(\frac{1}{5}\)

Question 22.

3 – \(\frac{3}{5}\) =

Answer:

3 – \(\frac{3}{5}\) = 2\(\frac{2}{5}\)

Explanation :

3 – \(\frac{3}{5}\) = \(\frac{15}{5}\) – \(\frac{3}{5}\) = \(\frac{12}{5}\) = 2\(\frac{2}{5}\)

Question 23.

3 – \(\frac{1}{8}\) =

Answer:

3 – \(\frac{1}{8}\) = 2\(\frac{7}{8}\)

Explanation :

3 – \(\frac{1}{8}\) = \(\frac{24}{8}\) – \(\frac{1}{8}\) = \(\frac{23}{8}\) = 2\(\frac{7}{8}\)

Question 24.

3 – \(\frac{3}{8}\) =

Answer:

3 – \(\frac{3}{8}\) = 2\(\frac{5}{8}\)

Explanation :

3 – \(\frac{3}{8}\) = \(\frac{24}{8}\) – \(\frac{3}{8}\) = \(\frac{21}{8}\) = 2\(\frac{5}{8}\)

Question 25.

3 – \(\frac{5}{8}\) =

Answer:

3 – \(\frac{5}{8}\) = 2\(\frac{3}{8}\)

Explanation :

3 – \(\frac{5}{8}\) = \(\frac{24}{8}\) – \(\frac{5}{8}\) = \(\frac{19}{8}\) = 2\(\frac{3}{8}\)

Question 26.

3 – \(\frac{7}{8}\) =

Answer:

3 – \(\frac{7}{8}\) = 2\(\frac{1}{8}\)

Explanation :

3 – \(\frac{7}{8}\) = \(\frac{24}{8}\) – \(\frac{7}{8}\) = \(\frac{17}{8}\) = 2\(\frac{1}{8}\)

Question 27.

2 – \(\frac{7}{8}\) =

Answer:

2 – \(\frac{7}{8}\) = 1\(\frac{1}{8}\)

Explanation :

2 – \(\frac{7}{8}\) = \(\frac{16}{8}\) – \(\frac{7}{8}\) = \(\frac{9}{8}\) = 1\(\frac{1}{8}\)

Question 28.

4 – \(\frac{1}{7}\) =

Answer:

4 – \(\frac{1}{7}\) = 3\(\frac{6}{7}\)

Explanation :

4 – \(\frac{1}{7}\) = \(\frac{28}{7}\) – \(\frac{1}{7}\) = \(\frac{27}{7}\) = 3\(\frac{6}{7}\)

Question 29.

3 – \(\frac{6}{7}\) =

Answer:

3 – \(\frac{6}{7}\) = 2\(\frac{1}{7}\)

Explanation :

3 – \(\frac{6}{7}\) = \(\frac{21}{7}\) – \(\frac{6}{7}\) = \(\frac{15}{7}\) = 2\(\frac{1}{7}\)

Question 30.

2 – \(\frac{3}{7}\) =

Answer:

2 – \(\frac{3}{7}\) =

Answer:

2 – \(\frac{3}{7}\) = 1\(\frac{4}{7}\)

Explanation :

2 – \(\frac{3}{7}\) = \(\frac{14}{7}\) – \(\frac{3}{7}\) = \(\frac{11}{7}\) = 1\(\frac{4}{7}\)

Question 31.

4 – \(\frac{4}{7}\) =

Answer:

4 – \(\frac{4}{7}\) =

Answer:

4 – \(\frac{4}{7}\) = 3\(\frac{3}{7}\)

Explanation :

4 – \(\frac{4}{7}\) = \(\frac{28}{7}\) – \(\frac{4}{7}\) = \(\frac{24}{7}\) = 3\(\frac{3}{7}\)

Question 32.

3 – \(\frac{5}{7}\) =

Answer:

3 – \(\frac{5}{7}\) = 2\(\frac{2}{7}\)

Explanation :

3 – \(\frac{5}{7}\) = \(\frac{21}{7}\) – \(\frac{5}{7}\) = \(\frac{16}{7}\) = 2\(\frac{2}{7}\)

Question 33.

4 – \(\frac{3}{4}\) =

Answer:

4 – \(\frac{3}{4}\) = 3\(\frac{1}{4}\)

Explanation :

4 – \(\frac{3}{4}\) = \(\frac{16}{4}\) – \(\frac{3}{4}\) = \(\frac{13}{4}\) = 3\(\frac{1}{4}\)

Question 34.

2 – \(\frac{5}{8}\) =

Answer:

2 – \(\frac{5}{8}\) = 1\(\frac{3}{8}\)

Explanation :

2 – \(\frac{5}{8}\) = \(\frac{16}{8}\) – \(\frac{5}{8}\) = \(\frac{11}{8}\) = 1\(\frac{3}{8}\)

Question 35.

3 – \(\frac{3}{10}\) =

Answer:

3 – \(\frac{3}{10}\) = 2\(\frac{7}{10}\)

Explanation :

3 – \(\frac{3}{10}\) = \(\frac{30}{10}\) – \(\frac{3}{10}\) = \(\frac{27}{10}\) = 2\(\frac{7}{10}\)

Question 36.

4 – \(\frac{2}{5}\) =

Answer:

4 – \(\frac{2}{5}\) = 3\(\frac{3}{5}\)

Explanation :

4 – \(\frac{2}{5}\) = \(\frac{20}{5}\) – \(\frac{2}{5}\) = \(\frac{18}{5}\) = 3\(\frac{3}{5}\)

Question 37.

4 – \(\frac{3}{7}\) =

Answer:

4 – \(\frac{3}{7}\) =

Answer:

4 – \(\frac{3}{7}\) = 3\(\frac{4}{7}\)

Explanation :

4 – \(\frac{3}{7}\) = \(\frac{28}{7}\) – \(\frac{3}{7}\) = \(\frac{25}{7}\) = 3\(\frac{4}{7}\)

Question 38.

3 – \(\frac{7}{10}\) =

Answer:

3 – \(\frac{7}{10}\) = 2\(\frac{3}{10}\)

Explanation :

3 – \(\frac{7}{10}\) = \(\frac{30}{10}\) – \(\frac{7}{10}\) = \(\frac{23}{10}\) = 2\(\frac{3}{10}\)

Question 39.

3 – \(\frac{5}{10}\) =

Answer:

3 – \(\frac{5}{10}\) = 2\(\frac{5}{10}\)

Explanation :

3 – \(\frac{5}{10}\) = \(\frac{30}{10}\) – \(\frac{5}{10}\) = \(\frac{25}{10}\) = 2\(\frac{5}{10}\)

Question 40.

4 – \(\frac{2}{8}\) =

Answer:

4 – \(\frac{2}{8}\) = 3\(\frac{6}{8}\)

Explanation :

4 – \(\frac{2}{8}\) = \(\frac{32}{8}\) – \(\frac{2}{8}\) = \(\frac{30}{8}\) = 3\(\frac{6}{8}\)

Question 41.

2 – \(\frac{9}{12}\) =

Answer:

2 – \(\frac{9}{12}\) = 2 – \(\frac{3}{4}\) = 1\(\frac{1}{4}\)

Explanation :

2 – \(\frac{3}{4}\) = \(\frac{8}{4}\) – \(\frac{3}{4}\) = \(\frac{5}{4}\) = 1\(\frac{1}{4}\)

Question 42.

4 – \(\frac{2}{12}\) = 3\(\frac{5}{6}\)

Answer:

4 – \(\frac{2}{12}\) = 4 – \(\frac{1}{6}\) = 3\(\frac{5}{6}\)

Explanation :

4 – \(\frac{1}{6}\) = \(\frac{24}{6}\) – \(\frac{1}{6}\) = \(\frac{23}{6}\) = 3\(\frac{5}{6}\)

Question 43.

3 – \(\frac{2}{6}\) =

Answer:

3 – \(\frac{2}{6}\) = 3 – \(\frac{1}{3}\) = 2\(\frac{2}{3}\)

Explanation :

3 – \(\frac{1}{3}\) = \(\frac{9}{3}\) – \(\frac{1}{3}\) = \(\frac{8}{3}\) = 2\(\frac{2}{3}\)

Question 44.

2 – \(\frac{8}{12}\) =

Answer:

2 – \(\frac{8}{12}\) = 2 – \(\frac{2}{3}\) = 1\(\frac{1}{3}\)

Explanation :

2 – \(\frac{2}{3}\) = \(\frac{6}{3}\) – \(\frac{2}{3}\) = \(\frac{4}{3}\) = 2\(\frac{1}{3}\)

B

Subtracting Fractions from a Whole Number

Question 1.

1 – \(\frac{1}{2}\) =

Answer:

1 – \(\frac{1}{2}\) = \(\frac{1}{2}\)

Explanation :

1 – \(\frac{1}{2}\) = \(\frac{2}{2}\) – \(\frac{1}{2}\) = \(\frac{1}{2}\)

Question 2.

2 – \(\frac{1}{2}\) =

Answer:

2 – \(\frac{1}{2}\) = 1\(\frac{1}{2}\)

Explanation :

2 – \(\frac{1}{2}\) = \(\frac{4}{2}\) – \(\frac{1}{2}\) = \(\frac{3}{2}\) = 1\(\frac{1}{2}\)

Question 3.

3 – \(\frac{1}{2}\) =

Answer:

3 – \(\frac{1}{2}\) = 2\(\frac{1}{2}\)

Explanation :

3 – \(\frac{1}{2}\) = \(\frac{6}{2}\) – \(\frac{1}{2}\) = \(\frac{5}{2}\) = 2\(\frac{1}{2}\)

Question 4.

4 – \(\frac{1}{2}\) =

Answer:

4 – \(\frac{1}{2}\) = 3\(\frac{1}{2}\)

Explanation :

4 – \(\frac{1}{2}\) = \(\frac{8}{2}\) – \(\frac{1}{2}\) = \(\frac{7}{2}\) = 3\(\frac{1}{2}\)

Question 5.

1 – \(\frac{1}{4}\) =

Answer:

1 – \(\frac{1}{4}\) = \(\frac{3}{4}\)

Explanation :

1 – \(\frac{1}{4}\) = \(\frac{4}{4}\) – \(\frac{1}{4}\) = \(\frac{3}{4}\)

Question 6.

2 – \(\frac{1}{4}\) =

Answer:

2 – \(\frac{1}{4}\) = 1\(\frac{3}{4}\)

Explanation :

2 – \(\frac{1}{4}\) = \(\frac{8}{4}\) – \(\frac{1}{4}\) = \(\frac{7}{4}\) = 1\(\frac{3}{4}\)

Question 7.

4 – \(\frac{1}{4}\) =

Answer:

4 – \(\frac{1}{4}\) = 3\(\frac{3}{4}\)

Explanation :

4 – \(\frac{1}{4}\) = \(\frac{16}{4}\) – \(\frac{1}{4}\) = \(\frac{15}{4}\) = 3\(\frac{3}{4}\)

Question 8.

4 – \(\frac{3}{4}\) =

Answer:

4 – \(\frac{3}{4}\) = 3\(\frac{1}{4}\)

Explanation :

4 – \(\frac{3}{4}\) = \(\frac{16}{4}\) – \(\frac{3}{4}\) = \(\frac{13}{4}\) = 3\(\frac{1}{4}\)

Question 9.

2 – \(\frac{3}{4}\) =

Answer:

2 – \(\frac{3}{4}\) = 1\(\frac{1}{4}\)

Explanation :

2 – \(\frac{3}{4}\) = \(\frac{8}{4}\) – \(\frac{3}{4}\) = \(\frac{5}{4}\) = 1\(\frac{1}{4}\)

Question 10.

2 – \(\frac{1}{3}\) =

Answer:

2 – \(\frac{1}{3}\) = 1\(\frac{2}{3}\)

Explanation :

2 – \(\frac{1}{3}\) = \(\frac{6}{3}\) – \(\frac{1}{3}\) = \(\frac{5}{3}\) = 1\(\frac{2}{3}\)

Question 11.

2 – \(\frac{2}{3}\) =

Answer:

2 – \(\frac{2}{3}\) = 1\(\frac{1}{3}\)

Explanation :

2 – \(\frac{2}{3}\) = \(\frac{6}{3}\) – \(\frac{2}{3}\) = \(\frac{4}{3}\) = 1\(\frac{1}{3}\)

Question 12.

3 – \(\frac{2}{3}\) =

Answer:

3 – \(\frac{2}{3}\) = 2\(\frac{1}{3}\)

Explanation :

3 – \(\frac{2}{3}\) = \(\frac{9}{3}\) – \(\frac{2}{3}\) = \(\frac{7}{3}\) = 2\(\frac{1}{3}\)

Question 13.

3 – \(\frac{1}{3}\) =

Answer:

3 – \(\frac{1}{3}\) = 2\(\frac{2}{3}\)

Explanation :

3 – \(\frac{1}{3}\) = \(\frac{9}{3}\) – \(\frac{1}{3}\) = \(\frac{8}{3}\) = 2\(\frac{2}{3}\)

Question 14.

4 – \(\frac{2}{3}\) =

Answer:

4 – \(\frac{2}{3}\) = 3\(\frac{1}{3}\)

Explanation :

4 – \(\frac{2}{3}\) = \(\frac{12}{3}\) – \(\frac{2}{3}\) = \(\frac{10}{3}\) = 3\(\frac{1}{3}\)

Question 15.

3 – \(\frac{1}{10}\) =

Answer:

3 – \(\frac{1}{10}\) = 2\(\frac{9}{10}\)

Explanation :

3 – \(\frac{1}{10}\) = \(\frac{30}{10}\) – \(\frac{9}{10}\) = \(\frac{21}{10}\) = 2\(\frac{1}{10}\)

Question 16.

2 – \(\frac{9}{10}\) =

Answer:

2 – \(\frac{9}{10}\) = 1\(\frac{1}{10}\)

Explanation :

2 – \(\frac{9}{10}\) = \(\frac{20}{10}\) – \(\frac{9}{10}\) = \(\frac{11}{10}\) = 1\(\frac{1}{10}\)

Question 17.

4 – \(\frac{7}{10}\) =

Answer:

4 – \(\frac{7}{10}\) = 3\(\frac{3}{10}\)

Explanation :

4 – \(\frac{7}{10}\) = \(\frac{40}{10}\) – \(\frac{7}{10}\) = \(\frac{33}{10}\) = 3\(\frac{3}{10}\)

Question 18.

3 – \(\frac{3}{10}\) =

Answer:

3 – \(\frac{3}{10}\) = 2\(\frac{7}{10}\)

Explanation :

3 – \(\frac{3}{10}\) = \(\frac{30}{10}\) – \(\frac{3}{10}\) = \(\frac{27}{10}\) = 2\(\frac{7}{10}\)

Question 19.

2 – \(\frac{1}{5}\) =

Answer:

2 – \(\frac{1}{5}\) = 1\(\frac{4}{5}\)

Explanation :

2 – \(\frac{1}{5}\) = \(\frac{10}{5}\) – \(\frac{1}{5}\) = \(\frac{9}{5}\) = 1\(\frac{4}{5}\)

Question 20.

2 – \(\frac{2}{5}\) =

Answer:

2 – \(\frac{2}{5}\) = 1\(\frac{3}{5}\)

Explanation :

2 – \(\frac{2}{5}\) = \(\frac{10}{5}\) – \(\frac{2}{5}\) = \(\frac{8}{5}\) = 1\(\frac{3}{5}\)

Question 21.

2 – \(\frac{4}{5}\) =

Answer:

2 – \(\frac{4}{5}\) = 1\(\frac{1}{5}\)

Explanation :

2 – \(\frac{1}{5}\) = \(\frac{10}{5}\) – \(\frac{4}{5}\) = \(\frac{6}{5}\) = 1\(\frac{1}{5}\)

Question 22.

3 – \(\frac{3}{5}\) =

Answer:

3 – \(\frac{3}{5}\) = 2\(\frac{2}{5}\)

Explanation :

3 – \(\frac{3}{5}\) = \(\frac{15}{5}\) – \(\frac{3}{5}\) = \(\frac{12}{5}\) = 2\(\frac{2}{5}\)

Question 23.

2 – \(\frac{1}{8}\) =

Answer:

2 – \(\frac{1}{8}\) = 1\(\frac{7}{8}\)

Explanation :

2 – \(\frac{1}{8}\) = \(\frac{16}{8}\) – \(\frac{1}{8}\) = \(\frac{15}{8}\) = 1\(\frac{7}{8}\)

Question 24.

2 – \(\frac{3}{8}\) =

Answer:

2 – \(\frac{3}{8}\) = 1\(\frac{5}{8}\)

Explanation :

2 – \(\frac{3}{8}\) = \(\frac{16}{8}\) – \(\frac{3}{8}\) = \(\frac{13}{8}\) = 1\(\frac{4}{8}\)

Question 25.

2 – \(\frac{5}{8}\) =

Answer:

2 – \(\frac{5}{8}\) = 1\(\frac{3}{8}\)

Explanation :

2 – \(\frac{5}{8}\) = \(\frac{16}{8}\) – \(\frac{5}{8}\) = \(\frac{11}{8}\) = 1\(\frac{3}{8}\)

Question 26.

2 – \(\frac{7}{8}\) =

Answer:

2 – \(\frac{7}{8}\) = 1\(\frac{1}{8}\)

Explanation :

2 – \(\frac{7}{8}\) = \(\frac{16}{8}\) – \(\frac{7}{8}\) = \(\frac{9}{8}\) = 1\(\frac{1}{8}\)

Question 27.

4 – \(\frac{7}{8}\) =

Answer:

4 – \(\frac{7}{8}\) = 3\(\frac{1}{8}\)

Explanation :

4 – \(\frac{7}{8}\) = \(\frac{32}{8}\) – \(\frac{3}{8}\) = \(\frac{13}{8}\) = 1\(\frac{4}{8}\)

Question 28.

3 – \(\frac{1}{7}\) =

Answer:

3 – \(\frac{1}{7}\) = 2\(\frac{6}{7}\)

Explanation :

3 – \(\frac{1}{7}\) = \(\frac{21}{7}\) – \(\frac{1}{7}\) = \(\frac{20}{7}\) = 2\(\frac{6}{7}\)

Question 29.

2 – \(\frac{6}{7}\) =

Answer:

2 – \(\frac{6}{7}\) = 1\(\frac{1}{7}\)

Explanation :

2 – \(\frac{6}{7}\) = \(\frac{14}{7}\) – \(\frac{6}{7}\) = \(\frac{8}{7}\) = 1\(\frac{1}{7}\)

Question 30.

4 – \(\frac{3}{7}\) =

Answer:

4 – \(\frac{3}{7}\) = 3\(\frac{4}{7}\)

Explanation :

4 – \(\frac{3}{7}\) = \(\frac{28}{7}\) – \(\frac{3}{7}\) = \(\frac{25}{7}\) = 3\(\frac{4}{7}\)

Question 31.

3 – \(\frac{4}{7}\) =

Answer:

3 – \(\frac{4}{7}\) = 2\(\frac{3}{7}\)

Explanation :

3 – \(\frac{4}{7}\) = \(\frac{21}{7}\) – \(\frac{4}{7}\) = \(\frac{17}{7}\) = 2\(\frac{3}{7}\)

Question 32.

2 – \(\frac{5}{7}\) =

Answer:

2 – \(\frac{5}{7}\) = 1\(\frac{2}{7}\)

Explanation :

2 – \(\frac{5}{7}\) = \(\frac{14}{7}\) – \(\frac{5}{7}\) = \(\frac{9}{7}\) = 1\(\frac{2}{7}\)

Question 33.

3 – \(\frac{3}{4}\) =

Answer:

3 – \(\frac{3}{4}\) = 2\(\frac{1}{4}\)

Explanation :

3 – \(\frac{3}{4}\) = \(\frac{12}{4}\) – \(\frac{3}{4}\) = \(\frac{9}{4}\) = 2\(\frac{1}{4}\)

Question 34.

4 – \(\frac{5}{8}\) =

Answer:

4 – \(\frac{5}{8}\) = 3\(\frac{3}{8}\)

Explanation :

4 – \(\frac{5}{8}\) = \(\frac{32}{8}\) – \(\frac{5}{8}\) = \(\frac{27}{8}\) = 3\(\frac{3}{8}\)

Question 35.

2 – \(\frac{3}{10}\) =

Answer:

2 – \(\frac{3}{10}\) = 1\(\frac{7}{10}\)

Explanation :

2 – \(\frac{3}{10}\) = \(\frac{20}{10}\) – \(\frac{3}{10}\) = \(\frac{17}{10}\) = 1\(\frac{7}{10}\)

Question 36.

3 – \(\frac{2}{5}\) =

Answer:

3 – \(\frac{2}{5}\) = 2\(\frac{3}{5}\)

Explanation :

3 – \(\frac{2}{5}\) = \(\frac{15}{5}\) – \(\frac{2}{5}\) = \(\frac{13}{5}\) = 2\(\frac{3}{5}\)

Question 37.

3 – \(\frac{3}{7}\) =

Answer:

3 – \(\frac{3}{7}\) = 2\(\frac{4}{7}\)

Explanation :

3 – \(\frac{3}{7}\) = \(\frac{21}{7}\) – \(\frac{3}{7}\) = \(\frac{18}{7}\) = 2\(\frac{4}{7}\)

Question 38.

2 – \(\frac{7}{10}\) =

Answer:

2 – \(\frac{7}{10}\) = 1\(\frac{3}{10}\)

Explanation :

2 – \(\frac{7}{10}\) = \(\frac{20}{10}\) – \(\frac{7}{10}\) = \(\frac{13}{10}\) = 1\(\frac{3}{10}\)

Question 39.

2 – \(\frac{5}{10}\) =

Answer:

2 – \(\frac{5}{10}\) = 1\(\frac{1}{2}\)

Explanation :

2 – \(\frac{5}{10}\) = \(\frac{20}{10}\) – \(\frac{5}{10}\) = \(\frac{15}{10}\) = \(\frac{3}{2}\) = 1\(\frac{1}{2}\)

Question 40.

3 – \(\frac{6}{8}\) =

Answer:

3 – \(\frac{6}{8}\) = 2\(\frac{1}{4}\)

Explanation :

3 – \(\frac{6}{8}\) = \(\frac{24}{8}\) – \(\frac{6}{8}\) = \(\frac{18}{8}\) = 2\(\frac{1}{4}\)

Question 41.

4 – \(\frac{3}{12}\) =

Answer:

4 – \(\frac{3}{12}\) = 4 – \(\frac{1}{4}\) = 3\(\frac{3}{4}\)

Explanation :

4 – \(\frac{1}{4}\) = \(\frac{16}{4}\) – \(\frac{1}{4}\) = \(\frac{15}{4}\) = 3\(\frac{3}{4}\)

Question 42.

3 – \(\frac{10}{12}\) =

Answer:

3 – \(\frac{10}{12}\) = 3 – \(\frac{5}{6}\) = 2\(\frac{1}{6}\)

Explanation :

3 – \(\frac{5}{6}\) = \(\frac{18}{6}\) – \(\frac{5}{6}\) = \(\frac{13}{6}\) = 2\(\frac{1}{6}\)

Question 43.

2 – \(\frac{4}{6}\) =

Answer:

2 – \(\frac{4}{6}\) = 2 – \(\frac{2}{3}\) = 1\(\frac{1}{3}\)

Explanation :

2 – \(\frac{2}{3}\) = \(\frac{6}{3}\) – \(\frac{2}{3}\) = \(\frac{4}{3}\) = 1\(\frac{1}{3}\)

Question 44.

4 – \(\frac{4}{12}\) =

Answer:

4 – \(\frac{4}{12}\) = 4 – \(\frac{1}{3}\) = 3\(\frac{2}{3}\)

Explanation :

4 – \(\frac{1}{3}\) = \(\frac{12}{3}\) – \(\frac{1}{3}\) = \(\frac{11}{3}\) = 3\(\frac{2}{3}\)

### Eureka Math Grade 5 Module 3 Lesson 5 Problem Set Answer Key

Question 1.

For the following problems, draw a picture using the rectangular fraction model and write the answer. Simplify your answer, if possible.

a. \(\frac{1}{3}\) – \(\frac{1}{4}\) =

b. \(\frac{2}{3}\) – \(\frac{1}{2}\) =

c. \(\frac{5}{6}\) – \(\frac{1}{4}\) =

d. \(\frac{2}{3}\) – \(\frac{1}{7}\) =

e. \(\frac{3}{4}\) – \(\frac{3}{8}\) =

f. \(\frac{3}{4}\) – \(\frac{2}{7}\) =

Answer:

a.

\(\frac{1}{3}\) – \(\frac{1}{4}\)

L.c.m of 3 and 4 is 12

\(\frac{4}{12}\) – \(\frac{3}{12}\) = \(\frac{1}{12}\)

b.

\(\frac{2}{3}\) – \(\frac{1}{2}\)

lcm of 3 and 2 is 6

\(\frac{4}{6}\) – \(\frac{3}{6}\) = \(\frac{1}{6}\)

c.

\(\frac{5}{6}\) – \(\frac{1}{4}\)

lcm of 6 and 4 is 12

\(\frac{10}{12}\) – \(\frac{3}{12}\) = \(\frac{7}{12}\)

d.

\(\frac{2}{3}\) – \(\frac{1}{7}\)

lcm of 3 and 7 is 21 .

\(\frac{14}{21}\) – \(\frac{3}{21}\)Â = \(\frac{11}{21}\)

e.

\(\frac{3}{4}\) – \(\frac{3}{8}\)

lcm of 4 and 8 is 8

\(\frac{6}{8}\) – \(\frac{3}{8}\) = \(\frac{3}{8}\)

f.

\(\frac{3}{4}\) – \(\frac{2}{7}\)

lcm of 4 and 7 is 28

\(\frac{21}{28}\) – \(\frac{8}{28}\) = \(\frac{13}{28}\)

Question 2.

Mr. Penman had \(\frac{2}{3}\) liter of salt water. He used \(\frac{1}{5}\) of a liter for an experiment. How much salt water does Mr. Penman have left?

Answer:

Quantity of salt water = \(\frac{2}{3}\)

Quantity of salt water used = \(\frac{1}{5}\)

Quantity of salt water left = \(\frac{2}{3}\) – \(\frac{1}{5}\) = \(\frac{10}{15}\) – \(\frac{3}{15}\)

= \(\frac{7}{15}\) .

Question 3.

Sandra says that \(\frac{4}{7}\) – \(\frac{1}{3}\) = \(\frac{3}{4}\) because all you have to do is subtract the numerators and subtract the denominators. Convince Sandra that she is wrong. You may draw a rectangular fraction model to support your thinking.

Answer:

No, \(\frac{4}{7}\) – \(\frac{1}{3}\) = \(\frac{5}{21}\) not \(\frac{3}{4}\)

Explanation :

\(\frac{4}{7}\) – \(\frac{1}{3}\) =Â \(\frac{12}{21}\) – \(\frac{7}{21}\) = Â \(\frac{5}{21}\)

no, first find the l.c.m of the denominators that is lcm of 7 and 3 is 21 . then multiply the denominators to make 21 and and also multiply same number with the numerator . then after making denominators equal subtract the numerators .

### Eureka Math Grade 5 Module 3 Lesson 5 Exit Ticket Answer Key

For the following problems, draw a picture using the rectangular fraction model and write the answer. Simplify your answer, if possible.

a. \(\frac{1}{2}\) – \(\frac{1}{7}\) =

b. \(\frac{3}{5}\) – \(\frac{1}{2}\) =

Answer:

a.

\(\frac{1}{2}\) – \(\frac{1}{7}\)

lcm of 2 and 7 is 14

\(\frac{7}{14}\) – \(\frac{2}{14}\) = \(\frac{5}{14}\)

b.

\(\frac{3}{5}\) – \(\frac{1}{2}\)

lcm of 5 and 2 is 10 .

\(\frac{6}{10}\) – \(\frac{5}{10}\) = \(\frac{1}{10}\)

### Eureka Math Grade 5 Module 3 Lesson 5 Homework Answer Key

Question 1.

The picture below shows \(\frac{3}{4}\) of the rectangle shaded. Use the picture to show how to create an equivalent fraction for \(\frac{3}{4}\), and then subtract \(\frac{1}{3}\).

\(\frac{3}{4}\) – \(\frac{1}{3}\) =

Answer:

Explanation :

\(\frac{3}{4}\) – \(\frac{1}{3}\)

l.c.m of 4 and 3 is 12

\(\frac{9}{12}\) – \(\frac{4}{12}\) = \(\frac{5}{12}\)

Question 2.

Find the difference. Use a rectangular fraction model to find common denominators. Simplify your answer, if possible.

a. \(\frac{5}{6}\) – \(\frac{1}{3}\) =

b. \(\frac{2}{3}\) – \(\frac{1}{2}\) =

c. \(\frac{5}{6}\) – \(\frac{1}{4}\) =

d. \(\frac{4}{5}\) – \(\frac{1}{2}\) =

e. \(\frac{2}{3}\) – \(\frac{2}{5}\) =

f. \(\frac{5}{7}\) – \(\frac{2}{3}\) =

Answer:

a.

\(\frac{5}{6}\) – \(\frac{1}{3}\)

Lcm of 6 and 3 is 6 .

\(\frac{5}{6}\) – \(\frac{2}{6}\) = \(\frac{3}{6}\) = \(\frac{1}{2}\)

b.

\(\frac{2}{3}\) – \(\frac{1}{2}\)

lcm of 3 and 2 is 6

\(\frac{4}{6}\) – \(\frac{3}{6}\) = \(\frac{2}{6}\) = \(\frac{1}{3}\)

c.

\(\frac{5}{6}\) – \(\frac{1}{4}\)

lcm of 6 and 4

\(\frac{10}{12}\) – \(\frac{3}{12}\) = \(\frac{7}{12}\)

d.

\(\frac{4}{5}\) – \(\frac{1}{2}\)

lcm of 5 and 2 is 10

\(\frac{8}{10}\) – \(\frac{5}{10}\) = \(\frac{3}{10}\)

e.

\(\frac{2}{3}\) – \(\frac{2}{5}\)

lcm of 3 and 5 is 15

\(\frac{10}{15}\) – \(\frac{6}{15}\)= \(\frac{4}{15}\)

f.

\(\frac{5}{7}\) – \(\frac{2}{3}\)

lcm of 7 and 3 is 21.

\(\frac{15}{21}\) – \(\frac{14}{21}\) = \(\frac{1}{21}\)

Question 3.

Robin used \(\frac{1}{4}\) of a pound of butter to make a cake. Before she started, she had \(\frac{7}{8}\) of a pound of butter. How much butter did Robin have when she was done baking? Give your answer as a fraction of a pound.

Answer:

Quantity of butter used to make cake = \(\frac{1}{4}\)Â pound

Quantity of butter with Robin before baking cake = \(\frac{7}{8}\)Â pound .

Total Quantity of butter with Robin after baking = \(\frac{7}{8}\)Â – \(\frac{1}{4}\) poundÂ = \(\frac{7}{8}\)Â – \(\frac{2}{8}\) = \(\frac{5}{8}\) pound

Therefore, Robin have \(\frac{5}{8}\) poundÂ when she was done baking .

Question 4.

Katrina needs \(\frac{3}{5}\) kilogram of flour for a recipe. Her mother has \(\frac{3}{7}\) kilogram of flour in her pantry. Is this enough flour for the recipe? If not, how much more will she need?

Answer:

Quantity of Flour Required for Recipe = \(\frac{3}{5}\)

Quantity of Flour with her mother = \(\frac{3}{7}\)

Quantity of Flour Enough or not = \(\frac{3}{7}\) – \(\frac{3}{5}\)Â = \(\frac{15}{35}\) – \(\frac{21}{35}\) = – \(\frac{6}{35}\) that means negative indicate doenot enough.

She needs more \(\frac{6}{35}\) Quantity of Flour for the Recipe .